Analysis of factors influencing the use of child restraint system by parents of children aged 0-6 years: an information, motivation, behavioral skills model-based cross-sectional study - Yaru Sun; Ting Liu; Junyu Chen; Juan Huang; Xin Wang; Mingqin Lu; Ying Luo; Xiuling Yang (BMC, 2023)
Abstract Background Children's injuries from traffic accidents have been identified as a global public health issue. Child restraint system (CRS) is a useful tool for lowering the risk of injury to children. Nevertheless, CRS usage is really low in China. The goal of the current study was to investigate the use of CRS after the legislation revised in China and to explore the influencing factors based on Information, Motivation, and Behavioral Skills model (IMB). Methods The study is a cross-sectional survey of parents who took their 0 to 6-year-old children for seeking primary care services at the Children Preventive Health Care Clinic of a tertiary hospital in Shandong Province, China. Parents were invited to complete the self-administered questionnaire between March and June 2022, including their knowledge, motivation, and behavioral skills, use behavior of CRS and socio-demographics. Ordinal logistic regression was used to explore the factors associated with CRS use by using SPSS software (version 26.0). Results In total, 442 parents participated in the study; 56.1% (n = 201) of the parents utilized CRS for their child passengers, however only 29.0% used CRS frequently. The result of logistic regression analysis show that parents with junior college (OR = 0.398, 95%CI: 0.185 ~ 0.857), possessing a high family economic status(OR = 0.225, 95%CI: 0.088 ~ 0.578), being trained on children's unintentional injuries(OR = 0.435,95%CI: 0.272 ~ 0.695), and having high scores on CRS riding mode cognition(OR = 0.476, 95%CI: 0.368 ~ 0.616), CRS type cognition(OR = 0.519, 95%CI: 0.392 ~ 0.689), CRS use motivation(OR = 0.392, 95%CI: 0.295 ~ 0.520) and installation skills(OR = 0.559, 95%CI:0.411 ~ 0.761) were the main factors promoting the usage of CRS. Conclusions This study found that the use of CRS can be increased by improving parents' knowledge, motivation and behavior skills and hence related educational programs is necessary for increasing CRS use in China.